2014
DOI: 10.1007/s00145-014-9192-y
|View full text |Cite
|
Sign up to set email alerts
|

Breaking RSA May Be As Difficult As Factoring

Abstract: If factoring is hard, then straight line programs cannot efficiently solve the low public exponent RSA problem. More precisely, no efficient algorithm can take an RSA public key as input and then output a straight line program that efficiently solves the low public exponent RSA problem for the given public key -unless factoring is easy. More generally, it suffices that the public exponent has a small factor. Of course, other kinds of algorithms may well be able to solve the RSA problem.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
15
0
2

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(17 citation statements)
references
References 10 publications
0
15
0
2
Order By: Relevance
“…Відкритий ключ містить ве-лике складене ціле число -криптомодуль N, що є добутком двох великих простих чисел. Натепер немає відомого простішого універсального способу зламати шифрування як факторизація N. Тоді можемо отримати два прості числа з добутку та розшифрувати повідомлення [7,8].…”
Section: вступunclassified
See 1 more Smart Citation
“…Відкритий ключ містить ве-лике складене ціле число -криптомодуль N, що є добутком двох великих простих чисел. Натепер немає відомого простішого універсального способу зламати шифрування як факторизація N. Тоді можемо отримати два прості числа з добутку та розшифрувати повідомлення [7,8].…”
Section: вступunclassified
“…Відкритий ключ містить ве-лике складене ціле число -криптомодуль N, що є добутком двох великих простих чисел. Натепер немає відомого простішого універсального способу зламати шифрування як факторизація N. Тоді можемо отримати два прості числа з добутку та розшифрувати повідомлення [7,8].У 1977 р., коли був винайдений алгоритм RSA, факторизація цілих чи-сел з 80-десятковими знаками здавалась неможливою; 256-бітові ключі були надійними. Першим суттєвим проривом стало квадратичне решето (Quadratic Sieve) [1] -метод, винайдений Карлом Померансом у 1981 р., який може факторизувати числа розміром 100 десяткових символів і більше.…”
unclassified
“…Fig.3 shows the models and methods of attack and defense in modern cryptography. Time and space compromise [3], collision attack, factorization, and computation of discrete logarithm are all common attack methods. In the middle meet attack on 2DES with 112 bit keys, the time decreased from 2 112 to 2 56 through storing 2*2 56 temporary ciphertexts.…”
Section: Attack and Defense In Modern Cryptographymentioning
confidence: 99%
“…Brown [5] showed that if factoring is hard then the LE-RSA problem is intractable for SLPs with Π = {+, −, ·}. More precisely, he proved that an efficient SLP for breaking LE-RSA can be transformed into an efficient factoring algorithm.…”
Section: Comparison With Related Workmentioning
confidence: 99%